Daya Saing Sektor Pertanian dalam Pembangunan Kota Tebing Tinggi Provinsi Sumatra Utara - LENI MARIA TARIGAN; I MADE SUDARMA; I NYOMAN GEDE USTRIYANA (Jurnal Agribisnis dan Agrowisata (Journal of Agribusiness and Agritourism), 2022)
Competitiveness of the Agricultural Sector in the Development of Tebing Tinggi City North Sumatra Province The rapid land conversion in the agricultural sector in Tebing Tinggi City indicates that the agricultural sector requires more efforts to support the development of Tebing Tinggi City. This study aims to determine the role of the agricultural sector, the leading sector, and the competitiveness of the agricultural sector and other sectors in Tebing Tinggi City for the 2015-2019 period. This study uses a descriptive method, the location quetient (LQ) method, and the shift share method. The results showed that the agricultural sector in Tebing Tinggi City was not the largest contributor and food crops played a major role in the growth of the agricultural sector. Tebing Tinggi City has 12 leading sectors and 5 non-sectors. In the future, there are 5 leading sectors, 7 prospective sectors, 5 lagging sectors, and no mainstay sector. Good competitive sectors, namely, wholesale and retail trade; repair of cars and motorcycles, and the health services sector and social activities. Research suggestions to maintain food security are important to use yards as community gardens, mikan ponds, and livestock, immediately implement the Culinary Tourism City concept, increase incentives or facilities that can support underdeveloped sectors, continue to pay attention to the development of leading sectors, and further research related to sector development strategies left behind.